Magnetic susceptibility of composite sediment core ROD11 from the crater basin of Rodderberg, Germany - Zolitschka, Bernd; Frechen, Manfred (PANGAEA, 2025)
Magnetic susceptibility – a proxy parameter for core correlation and reconstruction of glacial/interglacial cycles for the Middle Pleistocene sediment record from the crater basin of Rodderberg, Germany. A 72.8 m long sediment record was recovered by means of wire-line drilling with 3 m long liners from the silted-up crater basin of Rodderberg (East Eifel Volcanic Field) in the vicinity of the city of Bonn, Germany. The two drill holes (ROD11-2 and ROD11-3) were merged to establish a composite record (ROD11) based on macroscopic sediment description and were fine-tuned by magnetic susceptibility data. Magnetic susceptibility was continuously logged with 1 cm spatial resolution with a Bartington loop-sensor (MS2C) on a GEOTEK multi-sensor core-logger. Furthermore, this parameter facilitates the differentiation between glacial and interglacial sediments, thereby supporting the palaeoclimatic interpretation based on geochemical data spanning the past 430 ka. The combined evidence suggests a depositional evolution from a deep crater lake via a shallow lake or desiccating wetland followed by deposition of loess and pedogenesis. This terrestrial record, evaluated through multiple dating techniques, offers a comprehensive environmental reconstruction since the Middle Pleistocene.
Keywords: biogenic silica; carbonates; cluster analysis; crater lake; diatoms; East Eifel Volcanic Field; Germany; grainsize; Interglacials; lake sediment proxies; Magnetic susceptibility; minerogenic matter; organic matter; Palaeoclimate reconstructions; Pleistocene; XRF-core scanning